History of the Akkadian Language: Linguistic background and early periods - The second and first millennia BCE afterlife - Vita, Juan-Pablo (Handbuch der Orientalistik, 2021)
Akkadian is, after Sumerian, the second oldest language attested in the Ancient Near East, as well as the oldest known Semitic language. It is also a language with one of history's longest written records. And yet, unlike other relevant languages written over a long period of time, there has been no volume dedicated to its own history. The aim of the present work is to fill that void. The outcome is presented in 26 chapters written by 25 leading authors and divided into two volumes, the first covering the linguistic background and early periods and the second covering the second and first millennia BCE as well as its afterlife